2003
DOI: 10.1080/1042015021000052223
|View full text |Cite
|
Sign up to set email alerts
|

Fast Intrinsic Emissions of Wide-Gap Oxides Under Electron Irradiation

Abstract: . Da:f~l'k /3, 480/00 Almaty, Ka=akhstan .. 'The emission spectra have been measured in the range of 1.6 -9.0eV under irradiation of wide-gap oxides by single electron pulses (3 ns, 300 kV). A fast ( r < 3 ns) continuous and temperature-independent emission, connected mainly with the transitions of hot holes between the levels of the valence band of oxides, can be separated in these spectra at 300 600 K, when the inertial emissions (5-7 eV) of localized excitations undergo a strong thermal quenching. It is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The impurity emission peaked at 4.13 eV has been detected in a NaBr:Ca single crystal, while the emission of Mn 2+ and Eu 2+ centres has been registered in Zn 2 SiO 4 :Mn (see also [8]) and SAM:Eu powders, respectively. Our analysis with consideration of near-surface losses showed that in NaBr, one photon of 19 and 23 eV was able to create two or three e-h pairs, Table 2 Energy gap E g ; width of a valence band E v (in eV) and E v =E g ratio for some WGO [19] and AHC [18] respectively [20]. In Zn 2 SiO 4 :Mn and SAM:Eu, near-surface non-radiative recombinations are practically absent but the absolute QY of luminescence only doubles with the rise of the exciting photon energy from 15 eV up to hn ex ¼ 23 eV: According to Table 2, the parameter of ''hole losses'' in NaBr is E v =E g ¼ 0:48; while E v =E g ¼ 0:9 in SAM, i.e.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The impurity emission peaked at 4.13 eV has been detected in a NaBr:Ca single crystal, while the emission of Mn 2+ and Eu 2+ centres has been registered in Zn 2 SiO 4 :Mn (see also [8]) and SAM:Eu powders, respectively. Our analysis with consideration of near-surface losses showed that in NaBr, one photon of 19 and 23 eV was able to create two or three e-h pairs, Table 2 Energy gap E g ; width of a valence band E v (in eV) and E v =E g ratio for some WGO [19] and AHC [18] respectively [20]. In Zn 2 SiO 4 :Mn and SAM:Eu, near-surface non-radiative recombinations are practically absent but the absolute QY of luminescence only doubles with the rise of the exciting photon energy from 15 eV up to hn ex ¼ 23 eV: According to Table 2, the parameter of ''hole losses'' in NaBr is E v =E g ¼ 0:48; while E v =E g ¼ 0:9 in SAM, i.e.…”
Section: Article In Pressmentioning
confidence: 99%
“…on the basis of a short-wavelength edge of a fast (to1 ns) hole intra-band luminescence, connected with radiative transitions of holes inside the valence band [19]. The spectra of a hole intra-band luminescence have been measured at the excitation of WGO by nanosecond pulses of 300 keV electrons.…”
Section: Article In Pressmentioning
confidence: 99%